Assessment of the Contribution of Radiations of User Equipment to the Anthropogenic Electromagnetic Background Created by Mobile (Cellular) Communications - V. I. Mordachev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The declared increase in spatial density of user (terminal, peripheral, etc.) radiating equipment (UE) of mobile communications up to 0.1 UE/m2 in 4G (LTE) networks, up to 1.0 UE/m2 in 5G (NR) networks and up to 10 UE/m2 in promising 6G networks may cause an unacceptable increase in electromagnetic background and in corresponding forced risks to public health. The paper proposes a method for assessing the contribution of UE radiations to the level of anthropogenic electromagnetic background created by mobile communications. This method is based on the analysis of the electromagnetic loading on the area created by stationary and mobile radiation sources of mobile communications and determined by the area density of mobile traffic, its asymmetry in downlink and uplink data transmission, the degree of UE concentration in the observation point vicinity, the radio channels spectral efficiency, the size of base stations service areas and other characteristics. The calculated data are given, indicating that in places of UE concentration, the component of electromagnetic background formed by UE radiations may be predominant, many times exceeding the contribution of base station radiations, and determining the actual level of forced risks to public health, which requires consideration in the system of their hygienic rationing.